Perception of Educational Agents in Relation to Attention to Diversity in Educational Establishments - Cornejo-Valderrama, Carolina Genoveva de las Mercedes (2017)
This article aims to know the perception of educational agents in relation to the attention to diversity in educational establishments in the villages of Talca and Curicó (Chile). The sample was made up of 446 education professionals, grouped into managers, classroom teachers, and professionals in counseling for children and youth with special educational needs. The method implemented was non-experimental, for descriptive purposes, transactional, and a questionnaire was used as instrument for collecting information. The analysis of the information was done through frequency tables. As a conclusion, it can be said that educational agents have a favorable perception in relation to the attention to diversity; the concept of diversity is seen as an enriching element that allows flexibility of the curriculum, the interdisciplinary work, adjustment of the curricular requirements to the needs of students to generate learning opportunities for all students.